A mutant MATR3 mouse model to explain multisystem proteinopathy. Issue 2 (18th June 2019) - Zhang, Xiao; Yamashita, Satoshi; Hara, Kentaro; Doki, Tsukasa; Tawara, Nozomu; Ikeda, Tokunori; Misumi, Yohei; Zhang, Ziwei; Matsuo, Yoshimasa; Nagai, Makiko; Kurashige, Takashi; Maruyama, Hirofumi; et al.
Abstract: Mutations in the Matrin 3 ( MATR3 ) gene have been identified as a cause of amyotrophic lateral sclerosis (ALS) or vocal cord and pharyngeal weakness with distal myopathy (VCPDM). This study investigated the mechanism by which mutant MATR3 causes multisystem proteinopathy (MSP) including ALS and VCPDM. We first analyzed the muscle pathology of C57BL/6 mice injected with adeno‐associated viruses expressing human WT or mutant (S85C) MATR3 . We next generated transgenic mice that overexpress mutant (S85C) MATR3, driven by the CMV early enhancer/chicken β‐actin promoter, and evaluated their clinicopathological features. Intramuscular injection of viruses expressing WT and mutant MATR3 induced similar myogenic changes, including smaller myofibers with internal nuclei, and upregulated p62 and LC3‐II. Mutant MATR3 transgenic mice showed decreased body weight and lower motor activity. Muscle histology demonstrated myopathic changes including fiber‐size variation, internal nuclei and rimmed vacuoles. Spinal cord histology showed a reduced number of motor neurons, and activation of microglia and astrocytes. Comprehensive proteomic analyses of muscle demonstrated upregulation of proteins related to chaperones, stress response, protein degradation, and nuclear function. Overexpression of WT and mutant MATR3 similarly caused myotoxicity, recapitulating the clinicopathological features of MSP. These models will be helpful for analyzing MSP pathogenesis and for understanding the function of MATR3 . © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.